Durable Self-Cleaning Coatings for Architectural Surfaces by Incorporation of TiO(2) Nano-Particles into Hydroxyapatite Films - Sassoni, Enrico (Materials (Basel), 2018)
To prevent soiling of marble exposed outdoors, the use of TiO(2) nano-particles has been proposed in the literature by two main routes, both raising durability issues: (i) direct application to marble surface, with the risk of particle leaching by rainfall; (ii) particle incorporation into inorganic or organic coatings, with the risk of organic coating degradation catalyzed by TiO(2) photoactivity. Here, we investigated the combination of nano-TiO(2) and hydroxyapatite (HAP), previously developed for marble protection against dissolution in rain and mechanical consolidation. HAP-TiO(2) combination was investigated by two routes: (i) sequential application of HAP followed by nano-TiO(2) (“H+T”); (ii) simultaneous application by introducing nano-TiO(2) into the phosphate solution used to form HAP (“HT”). The self-cleaning ability was evaluated before and after prolonged exposure to simulated rain. “H+T” and “HT” coatings exhibited much better resistance to nano-TiO(2) leaching by rain, compared to TiO(2) alone. In “H+T” samples, TiO(2) nano-particles adhere better to HAP (having flower-like morphology and high specific surface area) than to marble. In “HT” samples, thanks to chemical bonds between nano-TiO(2) and HAP, the particles are firmly incorporated in the HAP coating, which protects them from leaching by rain, without diminishing their photoactivity and without being degraded by them.